La mariquita malhumorada - Carle, Eric. (New York : HarperCollins, 1992)
A grouchy ladybug who is looking for a fight challenges everyone she meets regardless of their size or strength. Text in Spanish.
Translation of: The grouchy ladybug.
Keywords: Ladybugs -- Juvenile fiction; Toy and movable books -- Specimens; Spanish language materials -- Juvenile fiction; Toy and movable books -- Juvenile fiction; Fiction